Electricity Demand in a Northern Mexico Metropolitan Economy - Fullerton, Thomas M.; Méndez-Carrillo, Ericka C.; Walke, Adam G. (International Journal of Energy Economics and Policy, 2014)
Using an error correction framework, this study analyzes the long- and short-run dynamics of electricity demand in Ciudad Juarez, a large metropolitan economy on Mexico’s northern border. Demand is decomposed into the total number of electricity accounts and electricity usage per customer, each of which is modeled separately. A two-stage least squares approach is used to estimate the per customer electricity demand equations due to the endogeneity of the average price variable. The results indicate sustained growth in population, employment, and income can be expected to exert substantial upward pressure on regional electric power demand. Furthermore, demand is found to be price-inelastic in this metropolitan area, suggesting that rate increases can help raise the revenues necessary to fund expansion of the electrical grid. Keywords: Electricity Demand; Urban Economics; Applied Econometrics; Mexico JEL Classifications: M21; Q41; R15